Systematic Approach to Address Early Pandemic's Diagnostic Unmet Needs - Cabrera, Catherine; Pilobello, Kanoelani; Dalvin, Steven; Bobrow, Johanna; Shah, Darshi; Garg, Lori Freed; Chalise, Sujata; Doyle, Patrick; Miller, Glenn A.; Walt, David R.; Suliman, Sara; Jolly, Pawan (Frontiers in Microbiology, 2022)
During the first few months of the global Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) pandemic, the medical research community had to expeditiously develop, select, and deploy novel diagnostic methods and tools to address the numerous testing challenges presented by the novel virus. Integrating a systematic approach to diagnostic selection with a rapid validation protocol in a clinical setting can shorten the timeline to bring new technologies to practice. In response to the urgent need to provide tools for identifying SARS-CoV-2-positive individuals, we developed a framework for assessing technologies against a set of prioritized performance metrics to guide device selection. We also developed and proposed clinical validation frameworks for the rapid screening of new technologies. The rubric described here represents a versatile approach that can be extended to future technology assessments and can be implemented in preparation for future emerging pathogens.